PENERAPAN DISKRESI KEPOLISIAN DALAM PENEGAKAN HUKUM PIDANA: TINJAUAN DARI UNDANG-UNDANG KEPOLISIAN DAN PERATURAN KAPOLRI - Nahwan Nahwan; Ilyas Ilyas; Ihlas Ihlas (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
Police discretion constitutes an inherently embedded authority instrument within Indonesia's criminal law enforcement system; however, its application frequently generates significant normative and empirical problematics. This study aims to comprehensively analyze the application of police discretion in criminal law enforcement through the normative framework of Law Number 2 of 2002 concerning the Indonesian National Police and the National Police Chief Regulations (Perkap), while identifying the gap between positive legal norms and field practice. This research employs a normative juridical approach with legal document analysis, cross-jurisdictional comparative study, and content analysis of selected jurisprudential decisions. The findings reveal that although police discretion has received juridical legitimation through Article 18 of the Police Act, its implementation remains constrained by the absence of measurable operational guidelines, comprehensive accountability mechanisms, and institutional capacity gaps at the implementation level. Furthermore, this study identifies a normative paradox whereby Kapolri regulations intended as operational guidelines contain ambiguous formulations that create space for discretion abuse. The novelty of this research lies in constructing an integrated conceptual framework between public administration discretion theory and criminal law within Indonesia's legal system context, along with proposing an accountability-based discretion regulation model. The study recommends regulatory reform through comprehensive Perkap issuance, standardized training system development, and strengthening synergistic internal-external oversight mechanisms. Keywords: Police Discretion; Criminal Law Enforcement; Police Act; Kapolri Regulation; Accountability; Legal Reform